Drinking Water Quality in Bangladesh | 2021 Updates - Charles, KJ (University of Oxford, 2021)
This report shares key findings from the Bangladesh Multiple Indicator Cluster Survey (MICS) 2019: Water Quality Thematic Report, based on water quality testing and survey carried out in 2019 by Bangladesh Bureau of Statistics (BBS) in collaboration with UNICEF and icddr,b. The Water Quality Thematic Report provides evidence of critical aspect of arsenic and faecal contamination (Escherichia coli or E.coli) of water supply and drinking water at the division and district levels. This publication presents information on arsenic and fecal contamination of drinking water at source and household level. It also provides relevant insights using the equity lens to examine the disparities between districts by key variables such as education, socioeconomic status as well as household water treatment and storage practices. The evidence presented facilitates planning, programming, advocacy and effective targeting of the most vulnerable and also serves as a bench mark for the SDG 6.1 “by 2030, achieve universal and equitable access to safe and affordable drinking water for all”.